Acute tubular necrosis: An old term in search for a new meaning within the evolving concept of acute kidney injury. Issue 4 (May 2015) - Sancho-Martínez, Sandra M.; Prieto, Laura; Blanco-Gozalo, Víctor; Fontecha-Barriuso, Miguel; Vicente-Vicente, Laura; Casanova, Alfredo G.; Prieto, Marta; Pescador, Moisés; Morales, Ana I.; López-Novoa, José M.; Martínez-Salgado, Carlos; López-Hernández, Francisco J.
Abstract: By the mid 2000s, the old term acute renal failure (ARF) was widened and superseded by the more inclusive concept of acute kidney injury (AKI). Whereas ARF referred to patients acutely needing dialysis to preserve life, AKI comprised all patients whose plasma creatinine concentration increased, or whose renal output decreased abruptly. This conceptual change primed clinical consideration, and stratification and handling criteria for a broader range of patients, hitherto not considered as such. A similar circumstance now lurks on the concept of acute tubular necrosis (ATN). ATN is the most common histo-functional pattern of a subtype of AKI, namely intrinsic AKI. In intrinsic AKI, the primary cause of AKI is posed by alterations in the renal parenchyma; as opposed to: (i) pre-renal AKI, in which the primary cause is a deficit of renal blood flow resulting from decreased perfusion pressure or glomerular hemodynamic alterations; and (ii) post-renal AKI, derived from obstruction of the urinary ways. The concept behind ATN has also evolved spontaneously, and without appropriate conceptual reconsideration, along with the evolution of AKI and the increasing knowledge of cell death modes. From the pristine concept of tubule cell necrotic death, ATN now even comprises syndromes and patterns involving sub-lethal alterations in tubule cells. This spontaneous evolution has blurred the conceptual boundaries of ATN and, most importantly, by doing so it has also nulled important stratification criteria, which are crucial for patient outcome. Prognosis of patients with mild, sub-lethal functional alterations may differ substantially from that of patients with extensive tissue destruction. Cataloging the whole range between both extremes under a unique ATN concept abrogates effective classification and care. By the mid 2010s, an international consensus redefinition of ATN with a severity scale, in which grades are associated to specific histo-functional alterations, seems timely and appropriate. Thereon, diagnostic criteria to discriminate ATN grades and handling recommendations must follow. Focal points: Benchside The term ATN has evolved spontaneously out of its initial semantic field in parallel to widening pathophysiological knowledge. Redefinition and sub-classification of ATN is necessary, which will refine histopathological studies in animal models and their translation to corresponding human conditions. Bedside An updated definition of ATN will help to more appropriately, more specifically and individually stratify patients, and apply personalized handling according to their pathophysiological process. Industry Translation of new ATN definition and sub-classification criteria into new and specific diagnostic tools is expected to broaden the market in the field and to provide new business opportunities. Government Sub-classification of ATN and development of specific diagnostic technologies may enable implementation of new standardized diagnostic protocols for AKI in public and private health systems, as appropriate. Regulatory Refinement of regulatory issues on nephrotoxicity on drug development may benefit from ATN redefinition and sub-classification, especially upon identification of ATN subtype markers.